1997
DOI: 10.1002/(sici)1099-0844(199712)15:4<259::aid-cbf749>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methotrexate (MTX) on NAD(P)+ dehydrogenases of HeLa cells: malic enzyme, 2-oxoglutarate and isocitrate dehydrogenases

Abstract: The effects of methotrexate (MTX) on oxygen uptake by permeabilized HeLa cells were evaluated. MTX did not inhibit state III respiration when the oxidizable substrate was succinate, but when the substrates were 2-oxoglutarate or isocitrate the respiration decreased about 50 per cent at 1.0 mM concentration of the drug. This effect was explained by inhibition of 2-oxoglutarate and isocitrate dehydrogenases by MTX. No effect was observed on succinate dehydrogenase. An evaluation of the effects of MTX on malic en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…It has been demonstrated that the cytosolic NAD(P)-dependent dehydrogenases (Vogel et al, 1963;Babiak et al, 1998) and NADP malic enzyme are inhibited by MTX, indicating that the drug could decrease the availability of NADPH in cells by inhibiting pentose cycle enzymes (Caetano et al, 1997). Due to the interference with the pentose phosphate shunt, MTX may also depress nucleic acid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the cytosolic NAD(P)-dependent dehydrogenases (Vogel et al, 1963;Babiak et al, 1998) and NADP malic enzyme are inhibited by MTX, indicating that the drug could decrease the availability of NADPH in cells by inhibiting pentose cycle enzymes (Caetano et al, 1997). Due to the interference with the pentose phosphate shunt, MTX may also depress nucleic acid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…8 The eect of MTX on several aspects of energy metabolism, in mitochondria and tumour cells, has been extensively investigated by several authors. 9±14 It is noteworthy that 2-oxoglutarate, pyruvate, isocitrate and malate dehydrogenases, 12,15,16 all NAD -dependent enzymes obtained from rat liver or HeLa cell mitochondria, are inhibited by MTX. Additionally, cytosolic NAD(P)-dependent dehydrogesases 17,18 are also inhibited by MTX.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that the NADP malic enzyme of HeLa cells is inhibited by MTX, suggesting that the drug could decrease the availability of NADPH in cells. 16 Malic enzyme and the pentose cycle are the main sources of NADPH in proliferating cells. 19 In addition, NADPH is used by glutathione reductase to maintain the reduced state of cell glutathione, which is known as an important protective agent against reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MTX treatment increases biomarkers associated with liver injury and are involving in hepatotoxicity [6]. MTX inhibits enzymes corresponding in production of the main sources of nicotine amide adenine dinucleotide (NADPH) resulting in intracellular decreases of NADPH [7]. Following NADPH decreasing, glutathione decreases and hepatocytes become vulnerable against reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%